Generation of altered transcripts by retroviral insertion within the c-myb gene in two murine monocytic leukemias. - Gonda, T J (1987)
Two murine monocytic leukemia cell lines, WEHI-265 and WEHI-274, were found to carry a rearranged c-myb gene. The rearrangements are due to insertion of a deleted Moloney murine leukemia virus (Mo-MLV) provirus in the 5' region of the c-myb gene and thus are similar to rearrangements in the ABPL tumors (G. L. C. Shen-Ong, M. Potter, J. F. Mushinski, S. Lavu, and E. P. Reddy, Science 226:1077-1080, 1984). In each cell line, the retroviral insertion has induced high levels of two aberrant RNA species, which, as in the ABPL tumors (G. L. C. Shen-Ong, H. C. Morse, M. Potter, and J. F. Mushinski, Mol. Cell. Biol. 6:380-392, 1986), contain both viral (Mo-MLV) and cellular (myb) sequences. Both species lack the sequences encoding the amino terminus of the c-myb protein and thus could encode a protein which, like the v-myb gene products (and the predicted ABPL myb proteins), is truncated at the amino terminus. We have found that the larger (5.3 kilobase [kb]) and more abundant of the tumor-specific myb RNAs was predominantly nuclear, while the smaller species (3.9 kb) was cytoplasmic. Furthermore, our data imply that the 3.9-kb RNA was derived from the 5.3-kb RNA by an additional splice which utilized a cryptic splice acceptor site within the viral gag sequences. On the basis of subcellular distribution and predicted translational potential, we conclude that the 3.9-kb RNA is probably the mRNA which encodes a truncated myb protein. We also show that, due to different insertion points in W265 and W274, the W274 myb RNAs contained sequences from a c-myb exon upstream of the exons represented in the W265 (and ABPL) RNAs. The significance of our findings with regard to transformation by myb in these tumors is discussed.